Megakaryocytic Alterations in Cases of Thrombocytopenia on Bone Marrow Examination at a Tertiary Care Centre - Ishita Choudhary; Sonal Bhati; Seema Meena; Monika Lukkad (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: Thrombocytopenia is a common hematological disorder characterized by the abnormal development of megakaryocytes, a crucial component of bone marrow. This study aims to analyze age-wise distribution, causes, megakaryocytic alterations, and dysplastic and non-dysplastic changes. Material and methods: This was a cross-sectional observational study conducted at the Department of Pathology, RNT Medical College, Udaipur, over six months. Bone marrow aspiration smears from 68 cases of thrombocytopenia were received and stained with Giemsa stain for 15-20 minutes. The examination was conducted under a light microscope to determine the number and morphology of megakaryocytes, and the findings were analyzed. Results: The commonest cause of thrombocytopenia was found to be acute leukemia (35.3%), followed by megaloblastic anemia (25%). The age-wise distribution of all cases showed a maximum number of cases belonging to the 21-30-year age group (26.5%). Cases with ITP presented with an increased number of megakaryocytes (100%). The decreased number was seen in the majority of cases of MDS (75%) and acute leukemia (62.5%). The total number of cases with dysplastic changes was 18 (26.5%), and that of non-dysplastic changes was 33 (48.5%). Conclusions: Megakaryocyte alterations in bone marrow aspirates from patients with thrombocytopenia underscore their clinical significance despite their small proportion in cellularity. A comprehensive evaluation is crucial for understanding the relationship between megakaryocyte alterations and the factors that cause thrombocytopenia, thereby enabling the development of effective treatment options.